Method for preparing sulfurized zero-valent iron with sulfur doped in iron body phase

By using lattice engineering and mechanical force chemistry technology to dopant sulfur elements into the body-center cubic structure in zero-valent iron, the problem of insufficient reactivity and selectivity of zero-valent iron in the prior art is solved, and more efficient Pollutant removal and material stability.

CN119263453AActive Publication Date: 2025-01-07TONGJI UNIV

Patent Information

Application Number
CN202411597016.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-07
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The prior art has limitations in improving the reactivity and selectivity of zero-valent iron, especially when dealing with complex pollutants, the internal electron transfer path of the material is not optimized, resulting in insufficient reaction efficiency and stability.

Method used

Using lattice engineering method, sulfur elements are doped into the body-center cubic structure of zero-valent iron through mechanical force chemistry technology, deeply changing the properties of the iron lattice, improving the reactive activity and selectivity of the material, and through wet ball milling method Achieve efficient sulfur doping.

Benefits of technology

It significantly improves the reaction performance of zero-valent iron and pollutant removal efficiency, ensures the stability of the material in long-term applications, reduces energy consumption and costs, and optimizes the electron transfer path.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263453A_ABST
    Figure CN119263453A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of sulfurized zero-valent iron doped with sulfur in an iron body phase, which comprises the following specific steps: S1, adding zero-valent iron, ferrous sulfide and pyrite into alcohol, and uniformly stirring to obtain slurry to be ground; s2, a grinding tank of a wet-process ball mill is filled with grinding beads, the slurry to be ground is added into the wet-process ball mill to be ground, vulcanized zero-valent iron particles are obtained, the grinding time is 40-640 min, the rotating speed of the wet-process ball mill is 1800-2200 rpm, a stirrer is arranged in the grinding tank, and the rotating speed of the stirrer is 100-140 rpm; s3, taking out the sulfurized zero-valent iron particles from the wet ball mill, and putting the sulfurized zero-valent iron particles into magnetic separation equipment for separation; and S4, the separated sulfurized zero-valent iron particles are washed with ethyl alcohol and placed in a vacuum drying box to be dried at the temperature of 55-65 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage treatment, and in particular to a method for preparing sulfided zero-valent iron doped with sulfur in an iron phase. Background Art

[0002] In the field of environmental remediation, zero-valent iron (ZVI) has become a common material for removing heavy metals, dechlorinating groundwater and industrial solvents due to its strong reducing ability, high abundance and environmental friendliness. However, the application of ZVI faces several key challenges. First, when ZVI reacts with water, it releases divalent iron ions (Fe2+) and hydrogen, resulting in a reduction in the number of electrons available for pollutant reduction, thereby reducing the reaction efficiency. In addition, in an alkaline, oxygen-rich environment, an insoluble iron (hydroxide) passivation layer is formed on the surface of ZVI. This passivation layer not only increases the resistance to pollutant mass transfer, but also forms a potential barrier between the iron and pollutant interfaces, further hindering the effective transfer of electrons.

[0003] To overcome these limitations and improve the reactivity and selectivity of ZVI, researchers have attempted to connect Fe with P-block elements such as sulfur at the atomic level.

[0004] Figure 1 Schematic diagram of surface-modified zero-valent iron sulfide. Figure 2 This is a schematic diagram of surface-modified zero-valent iron sulfide at different pH values.

[0005] The introduction of sulfur has been shown to significantly enhance the reactivity of ZVI, especially through surface modification and lattice engineering, such as Figure 1-2 As shown in Figure 2, surface modification is usually achieved by liquid phase precipitation, that is, the FeSx heterostructure is formed on the surface of ZVI through the decomposition, hydrolysis and disproportionation reaction of sulfur-containing precursors. This structure can serve as a bridge for electron transfer, transferring the electrons of iron to the target pollutant. However, this modification method is usually limited to the surface of ZVI and cannot effectively change the internal electronic structure of ZVI.

[0006] The Chinese invention patent with application number 202410541993.7 discloses a sulfide micron zero-valent iron and its preparation method and application. Sodium dithionite and iron powder are mixed and dry-milled to obtain sulfide micron zero-valent iron.

[0007] The invention does not consider the regulation of the zero-valent iron lattice structure during the preparation process. This lack leads to the failure to optimize the internal electronic structure of the material, which in turn limits the electron transfer efficiency and the overall reactivity of the material. In addition, since lattice engineering methods are not used, the reactivity and selectivity of the material rely on traditional surface modification or other surface treatment technologies, which cannot deeply change the core properties of the material, especially when dealing with complex pollutants such as Cr(VI) and TCE, the reaction rate and removal effect may be low.

[0008] The Chinese invention patent with application number 201910811326.5 discloses a preparation method and application of a sulfurized modified zero-valent iron composite material. Pyrite and zero-valent iron are mixed in a certain mass ratio and placed in a ball mill; ball milling beads are added to mix the pyrite and zero-valent iron evenly, and then dry-milled directly.

[0009] This invention adopts a traditional synthesis method. Although the method is mature, it usually has limitations in the microstructure and reactivity of the material. In particular, it may be difficult to reach the optimal level in terms of electron transfer efficiency and reaction activity. In addition, traditional methods are usually unable to finely control the lattice structure of the material, which means that the electron transfer pathway inside the material is not optimized, which may limit the efficiency of the material in treating complex pollutants. It may show lower stability and reaction efficiency in long-term applications and is difficult to adapt to the complex and changeable conditions in environmental remediation.

[0010] Therefore, the technical problem that needs to be solved urgently is: how to deeply change the core properties of the material and optimize the electron transfer pathway within the material, so as to improve its reduction ability and pollutant removal efficiency. Summary of the invention

[0011] The present invention is made to solve the above problems, and its purpose is to provide a method for preparing sulfided zero-valent iron doped with sulfur in the iron phase.

[0012] The present invention provides a method for preparing sulfur-doped zero-valent iron sulfide in an iron phase, which has the following characteristics and specific steps: S1, adding zero-valent iron, ferrous sulfide and pyrite into alcohol and stirring evenly to obtain a slurry to be ground; S2, filling a grinding jar of a wet ball mill with grinding beads, adding the slurry to be ground into the wet ball mill for grinding to obtain zero-valent iron sulfide particles, the grinding time is 40-640 minutes, the rotation speed of the wet ball mill is 1800-2200 rpm, and a stirrer is provided in the grinding jar, and the rotation speed of the stirrer is 100-140 rpm; S3, taking out the zero-valent iron sulfide particles from the wet ball mill, and placing the zero-valent iron sulfide particles into a magnetic separation device for separation; and S4, washing the separated zero-valent iron sulfide particles with ethanol, placing them in a vacuum drying oven, and drying them at a temperature of 55-65°C.

[0013] In the preparation method of sulfur-doped zero-valent iron sulfide provided by the present invention, it can also have the following characteristics: a wet ball mill includes a ball milling chamber for loading ball milling beads and slurry to be milled, and a stirring shaft for stirring the ball milling beads and the slurry to be milled is provided inside the ball milling chamber; a feed tank, one end of which is connected to the ball milling chamber and is used to input the slurry to be milled into the ball milling chamber, and a stirrer for uniformly stirring the slurry to be milled is provided in the feed tank; and a centrifugal pump, one end of which is connected to the ball milling chamber and the other end of which is connected to the other end of the feed tank, and the centrifugal pump is used to promote the slurry after ball milling in the ball milling chamber to return to the liquid storage tank to form a circulation.

[0014] In the method for preparing sulfur-doped zero-valent iron sulfide provided by the present invention, the method may also have the following feature: the rotation speed of the stirrer is 100-140 rpm.

[0015] The method for preparing sulfur-doped zero-valent iron provided by the present invention may also have the following characteristics: wherein the zero-valent iron is flaky micron-sized zero-valent iron.

[0016] The method for preparing sulfur-doped zero-valent iron sulfide provided by the present invention may also have the following characteristics: wherein the grinding beads are zirconium oxide grinding beads with a diameter of 0.3-0.5 mm, and the filling amount of the grinding beads is 0.7-0.8 kg.

[0017] The method for preparing sulfur-doped zero-valent iron sulfide provided by the present invention may also have the following characteristics: wherein the temperature of the grinding jar of the wet grinder is controlled at 22-28°C.

[0018] In the method for preparing sulfur-doped zero-valent iron sulfide provided by the present invention, the method may also have the following characteristics: wherein the mass ratio of ferrous sulfide, pyrite and zero-valent iron is 1:(0.9-1.1):(15.5-16).

[0019] Functions and Effects of the Invention

[0020] According to a method for preparing sulfide zero-valent iron doped with sulfur in the iron phase involved in the present invention, the present invention adopts a lattice engineering method, especially using mechanochemical technology, to effectively dope sulfur into the body-centered cubic structure of zero-valent iron, which not only affects the surface of the material, but also deeply changes the properties inside the iron lattice, so that the material has higher reactivity and selectivity when treating complex pollutants. Specifically, lattice engineering provides a more in-depth improvement approach. By inducing sulfur elements to enter the body-centered cubic (BCC) structure of Fe, the crystal structure of zero-valent iron and its geometric and electronic properties can be finely controlled. The doping of sulfur elements in the Fe lattice can not only enhance the conductivity of Fe, but also increase the electron mobility by forming pd hybrid orbits, thereby improving the overall reaction performance of zero-valent iron. At the same time, through the mechanochemical method, we can achieve efficient sulfur doping in a shorter preparation time, significantly reduce energy consumption and cost, and improve material preparation efficiency. The present invention can accurately control the doping amount of sulfur elements, which not only improves the initial activity of the material, but also ensures the stability of the material in long-term applications, avoiding the common efficiency reduction problem in traditional methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a schematic diagram of surface-modified sulfide zero-valent iron;

[0022] Figure 2 This is a schematic diagram of surface-modified zero-valent iron sulfide at different pH values;

[0023] Figure 3 It is a structural schematic diagram of a wet ball mill of the present invention;

[0024] Figure 4 is a schematic diagram comparing surface modification and the lattice engineering preparation method of the present invention;

[0025] Figure 5 is a transmission electron microscope photograph of zero-valent iron sulfide in Example 1 of the present invention;

[0026] Figure 6 is a transmission electron microscope photograph of zero-valent iron sulfide in Example 5 of the present invention;

[0027] Figure 7 is a comparison of the sulfur content of the sulfided zero-valent iron in Examples 1-5 of the present invention and Comparative Examples 1-5;

[0028] Figure 8 are X-ray diffraction (XRD) and Raman spectrum analysis diagrams of zero-valent iron sulfide in Example 1, Example 5, Comparative Example 1 and Comparative Example 5 of the present invention;

[0029] Fig. 9A comparative analysis of the reaction performance and electrochemical behavior of zero-valent iron sulfide in treating Cr(VI) and TCE pollutants in Examples 1-5 of the present invention and Comparative Examples 1-5;

[0030] Fig.10 The removal effects of Example 1, Example 5, Comparative Example 6 and Comparative Example 7 of the present invention on Cr; and

[0031] Fig.11 The figures are the removal effects of Example 1, Example 5, Comparative Example 6 and Comparative Example 7 of the present invention on TCE. DETAILED DESCRIPTION

[0032] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0033] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following examples and drawings specifically illustrate the preparation method of the present invention for preparing sulfur-doped zero-valent iron sulfide.

[0034] Figure 3 It is a structural schematic diagram of the wet ball mill of the present invention.

[0035] like Figure 3 As shown, the wet ball mill 100 used in the above method of the present invention includes a ball milling chamber 10 , a feed tank 30 and a centrifugal pump 20 .

[0036] The user first stirs the slurry to be ground, including zero-valent iron, ferrous sulfide, pyrite and alcohol, to form the slurry to be ground, and puts it into the feed tank 30. The feed tank 30 is provided with a stirrer 31 for stirring the slurry to be ground evenly. The rotation speed of the stirrer 31 is 120 rpm to avoid solid precipitation in the slurry to be ground. One end of the feed tank 30 is connected to the ball milling chamber 10, and the slurry to be ground is input into the ball milling chamber 10.

[0037] The ball milling chamber 10 is used to load ball milling beads and the slurry to be milled. A stirring shaft 11 is provided inside the ball milling chamber 10 for stirring the ball milling beads and the slurry to be milled. The stirring shaft rotates at 2000 rpm to ball mill the slurry to be milled.

[0038] The other end of the ball milling chamber 10 is connected to the centrifugal pump 20 , and the slurry after ball milling enters the centrifugal pump 20 , and then returns to the liquid storage tank 30 through the centrifugal pump 20 , forming a cycle.

[0039] Figure 4 It is a comparative schematic diagram of the surface modification and the lattice engineering preparation method of the present invention.

[0040] like Figure 4 As shown, the method for preparing sulfur-doped zero-valent iron of the present invention specifically comprises the following steps:

[0041] S1, adding flaky micron-sized zero-valent iron, ferrous sulfide and pyrite into alcohol and stirring evenly to obtain a slurry to be ground.

[0042] S2, filling the grinding tank of the wet ball mill with zirconium oxide grinding beads with a diameter of 0.3-0.5 mm and a filling amount of 0.7-0.8 kg, adding the slurry to be ground into the wet ball mill for grinding to obtain zero-valent iron sulfide particles, the grinding time is 40-640 min, and the grinding temperature is controlled at 22-28°C.

[0043] S3, taking out the zero-valent iron sulfide particles from the wet ball mill, and placing the zero-valent iron sulfide particles into a magnetic separation device for separation.

[0044] S4, placing the separated zero-valent iron sulfide particles in a vacuum drying oven and drying them at a temperature of 55-65°C.

[0045] Example 1

[0046] The method for preparing sulfur-doped zero-valent iron in the iron phase specifically comprises the following steps:

[0047] S1, add 3 g of flaky micron-sized zero-valent iron, 0.19 g of ferrous sulfide and 0.19 g of pyrite into 300 ml of alcohol and stir evenly to obtain a slurry to be ground.

[0048] S2, fill the grinding jar of the wet ball mill with zirconium oxide grinding beads with a diameter of 0.4 mm, the filling amount is 0.75 kg, add the slurry to be ground into the wet ball mill for grinding to obtain zero-valent iron sulfide particles, the rotation speed of the wet ball mill is 2000 rpm, the grinding jar is provided with an agitator, the rotation speed of the agitator is 120 rpm, the grinding temperature is controlled at 25°C, and the zero-valent iron sulfide particle sample is taken out after the grinding time is 40 minutes.

[0049] S3, placing the zero-valent iron sulfide particle sample into a magnetic separation device for separation.

[0050] S4, washing the separated zero-valent iron sulfide particle samples with ethanol, and placing them in a vacuum drying oven and drying them at a temperature of 60°C.

[0051] Example 2

[0052] On the basis of Example 1, "taking out the sample of zero-valent iron sulfide particles at a grinding time of 40 minutes" is replaced by "taking out the sample of zero-valent iron sulfide particles at a grinding time of 80 minutes".

[0053] Example 3

[0054] On the basis of Example 1, “taking out the sulfide zero-valent iron particle sample at a grinding time of 40 minutes” is replaced by “taking out the sulfide zero-valent iron particle sample at a grinding time of 160 minutes”.

[0055] Example 4

[0056] Based on Example 1, “taking out a sample of the zero-valent iron sulfide particles at a grinding time of 40 minutes” is replaced by “taking out a sample of the zero-valent iron sulfide particles at a grinding time of 320 minutes”.

[0057] Example 5

[0058] On the basis of Example 1, "taking out the sulfide zero-valent iron particle sample at a grinding time of 40 minutes" is replaced by "taking out the sulfide zero-valent iron particle sample at a grinding time of 640 minutes".

[0059] Comparative Example 1

[0060] The surface-modified zero-valent iron sulfide prepared by stirring specifically comprises the following steps:

[0061] S1, add 3 g of flaky micron-sized zero-valent iron, 0.19 g of ferrous sulfide and 0.19 g of pyrite into 300 ml of alcohol and stir evenly, and take out the zero-valent iron sulfide particle sample after the stirring time is 40 min.

[0062] S2, placing the zero-valent iron sulfide particle sample into a magnetic separation device for separation.

[0063] S3, washing the separated zero-valent iron sulfide particle samples with ethanol, and placing them in a vacuum drying oven and drying them at a temperature of 60°C.

[0064] Comparative Example 2

[0065] On the basis of Comparative Example 1, “taking out a sample of zero-valent iron sulfide particles at a grinding time of 40 minutes” was replaced by “taking out a sample of zero-valent iron sulfide particles at a grinding time of 80 minutes”.

[0066] Comparative Example 3

[0067] On the basis of Comparative Example 1, “taking out a sample of zero-valent iron sulfide particles at a grinding time of 40 minutes” was replaced by “taking out a sample of zero-valent iron sulfide particles at a grinding time of 160 minutes”.

[0068] Comparative Example 4

[0069] On the basis of Comparative Example 1, “taking out a sample of zero-valent iron sulfide particles at a grinding time of 40 minutes” was replaced by “taking out a sample of zero-valent iron sulfide particles at a grinding time of 320 minutes”.

[0070] Comparative Example 5

[0071] On the basis of Comparative Example 1, “taking out a sample of zero-valent iron sulfide particles at a grinding time of 40 minutes” was replaced by “taking out a sample of zero-valent iron sulfide particles at a grinding time of 640 minutes”.

[0072] Comparative Example 6

[0073] Based on Example 5, “0.19 g ferrous sulfide and 0.19 g pyrite” was replaced with “0.38 g pyrite”.

[0074] Comparative Example 7

[0075] Based on Example 5, “0.19 g ferrous sulfide and 0.19 g pyrite” was replaced with “0.38 g ferrous sulfide”.

[0076] Figure 5 This is a transmission electron microscope photograph of zero-valent iron sulfide in Example 1 of the present invention. Figure 6 This is a transmission electron microscope photograph of zero-valent iron sulfide in Example 5 of the present invention.

[0077] like Figure 5-6 As shown, the element distribution mapping analysis of the samples ball-milled for 40 minutes and 640 minutes was carried out by transmission electron microscopy (TEM), and the results showed a significant difference in the penetration of sulfur element in the zero-valent iron phase.

[0078] After 40 min of ball milling, sulfur element mainly showed sporadic local distribution, concentrated in certain areas of iron particles, indicating that sulfur only began to penetrate into the surface of iron lattice or the bulk phase near the surface at this stage.

[0079] As the ball milling time was extended to 640 minutes, the distribution of sulfur became more uniform and fully penetrated into the bulk of iron. This uniform distribution confirmed the deep penetration of sulfur into the iron lattice, which significantly changed the internal structure of the material. The iron element maintained a uniform distribution throughout the ball milling process, indicating that the mechanochemical treatment did not cause the migration or structural damage of iron. These TEM results provide direct bulk evidence that the mechanochemical method effectively doped sulfur into the iron lattice, thereby optimizing the material's electron transfer performance and reactivity.

[0080] Figure 7 It is a comparison of the sulfur content of the sulfided zero-valent iron in Examples 1-5 of the present invention and Comparative Examples 1-5.

[0081] like Figure 7 As shown in the figure, by comparing the sulfur content of surface-modified zero-valent iron sulfide (S-SZVI) prepared by stirring and bulk-doped zero-valent iron sulfide (M-SZVI) prepared by mechanochemical ball milling, the significant difference in sulfur doping efficiency between the two can be clearly seen. Within the same treatment time, the sulfur content of M-SZVI increases significantly faster than that of S-SZVI.

[0082] Specifically, after 40 min of ball milling treatment, the sulfur content in M-SZVI has reached 0.743%, which is much higher than 0.009% of S-SZVI.

[0083] As the ball milling time was extended to 640 minutes, the sulfur content of M-SZVI further increased to 3.802%, which is dozens of times the sulfur content of S-SZVI (0.047%) in the same time. This result highlights the excellent performance of the mechanochemical method in quickly achieving high sulfur doping, breaking through the limitations of traditional surface modification technology in sulfur content, and enabling the preparation of sulfided zero-valent iron to achieve unprecedented high S content in a short time. This significant growth and breakthrough is of great significance for optimizing the reaction performance of materials and expanding their application range.

[0084] Figure 8 These are X-ray diffraction (XRD) and Raman spectrum analysis diagrams of the sulfide zero-valent iron in Example 1, Example 5, Comparative Example 1 and Comparative Example 5 of the present invention.

[0085] like Figure 8 As shown, the sample processed by mechanochemical ball milling (M-SZVI) exhibits significant differences in the crystal phase and molecular vibration characteristics compared with the surface modified sample prepared by stirring (S-SZVI).

[0086] In the XRD graph (A), the diffraction peak intensities of FeS and FeS2 in the M-SZVI sample are significantly higher than those in the S-SZVI sample, especially after 640 minutes of ball milling, the FeS2 peak of the M-SZVI sample is significantly enhanced, indicating that a more stable and ordered sulfide crystal phase is formed in the bulk phase. These results confirm that mechanochemical treatment can effectively promote the deep doping of sulfur in the iron bulk phase and generate a variety of stable sulfide phases.

[0087] In the Raman spectrum (B), the symmetric stretching vibration peaks of the Fe-S bonds at 216cm-1 and 288cm-1 of the M-SZVI sample are significantly stronger and slightly red-shifted, indicating that as sulfur gradually penetrates into the bulk phase, the coordination environment of the Fe-S bonds changes significantly, further enhancing the structural stability of the iron sulfide.

[0088] In contrast, the Fe-S bond peak in the S-SZVI sample is weak and lacks significant lattice regulation features, indicating that the surface modification method has limitations in promoting sulfur doping in the iron phase and lattice optimization.

[0089] Overall, these analysis results highlight that the mechanochemical treatment not only effectively achieves uniform doping of sulfur in the bulk phase, but also significantly improves the material's lattice structure and reaction performance.

[0090] Fig. 9 It is a comparative analysis of the reaction performance and electrochemical behavior of the sulfide zero-valent iron of Examples 1-5 of the present invention and Comparative Examples 1-5 when treating Cr(VI) and TCE pollutants.

[0091] like Fig. 9 As shown in Figure (A), the experimental results of Cr(VI) removal clearly show that the reaction rate of the M-SZVI_640 sample is significantly faster than that of other samples. After 50 minutes of reaction, the M-SZVI_640 sample almost completely removed Cr(VI), while the S-SZVI_640 sample only removed about 20% of Cr(VI) in the same time. The removal efficiency of the M-SZVI_40 sample is also significantly higher than that of the S-SZVI_40 sample prepared in the same time. The k_obs (reaction rate constant) illustration in the figure further quantifies this difference. The rate constant of M-SZVI_640 is as high as 0.0850min-1, which is more than 20 times that of S-SZVI_640, indicating that the mechanochemical treatment significantly improves the reactivity of the material.

[0092] In Figure (B), the TCE removal experiment also shows a similar trend. The M-SZVI_640 sample reduced the TCE concentration from the initial value to nearly 50% within 50 minutes, while the S-SZVI_640 sample only decreased slightly. The removal efficiency of the M-SZVI_40 and M-SZVI_640 samples was significantly better than that of the corresponding S-SZVI samples, with reaction rate constants k_obs of 0.0210min-1 and 0.0140min-1, respectively, while the k_obs of S-SZVI_640 and S-SZVI_40 were only 0.0049min-1 and 0.0020min-1. This result shows that bulk-doped M-SZVI also exhibits higher reaction rate and efficiency in removing TCE, thanks to the uniform distribution of sulfur elements in the bulk phase, which significantly enhances the reactivity of the material.

[0093] The Tafel plot in Figure (C) further reveals the advantages of the M-SZVI sample in electrochemical behavior. The M-SZVI_640 sample shows a more negative corrosion potential (Ecorr) and a higher corrosion current density, indicating that it has a stronger electron donor ability and a more active electrochemical reaction. This result is consistent with the removal experiments of Cr(VI) and TCE, indicating that the mechanochemical ball milling treatment not only improves the deep penetration of sulfur in the iron lattice, but also effectively enhances the electron transfer ability of iron, thereby improving the overall reaction performance of the material in a complex environment. In contrast, the S-SZVI sample has relatively weak reactivity and electron transfer ability because the sulfur element is mainly concentrated on the surface and fails to significantly improve the internal electronic structure of the material.

[0094] In general, these experimental data fully demonstrate the excellent performance of M-SZVI in treating pollutants, especially in the removal of Cr(VI) and TCE, with a reaction rate and efficiency significantly better than that of the traditional surface-modified S-SZVI samples. This is attributed to the mechanochemical treatment method that effectively and uniformly doped sulfur into the bulk phase of zero-valent iron, significantly optimizing the material's lattice structure and electron transfer path, and improving the material's overall reactivity and electrochemical stability.

[0095] Fig.10 The Cr removal effects of Example 1, Example 5, Comparative Example 6 and Comparative Example 7 of the present invention are shown. Fig.11 The figures are the removal effects of Example 1, Example 5, Comparative Example 6 and Comparative Example 7 of the present invention on TCE.

[0096] like Figure 10-11 As shown, M-SZVI 40 Example 1, M-SZVI 640 Example 5, SZVI 640 -(D1) represents comparative example 6, SZVI 640-(D2) represents Comparative Example 7.

[0097] like Figure 7 As shown, M-SZVI 40 (red hollow dots) and M-SZVI 640 (Red solid squares): Both samples showed significant Cr(VI) removal capabilities, rapidly reducing Cr(VI) concentrations to below approximately 0.2C0 within 20 minutes of the start of the reaction. The removal rate continued to increase over time, eventually reaching near-complete removal.

[0098] SZV 640 (D1) (dark blue solid triangle) and SZVI 640 (D2) (light blue inverted triangle): Compared with the M-SZVI sample, the removal efficiency of these two samples is lower, especially in the first 40 minutes, the Cr(VI) concentration decreases slowly, and the final removal rate is also much lower than that of M-SZVI. 40 and M-SZVI 640 .

[0099] like Figure 8 As shown, M-SZVI 40 and M-SZVI 640 :In terms of TCE removal, M-SZVI 40 and M-SZVI 640 The removal rate also showed excellent performance, especially in the first 40 minutes, the TCE concentration dropped rapidly and the final concentration was close to 0, showing a very strong removal ability.

[0100] SZV 640 (D1) and SZVI 640 (D2): Samples prepared with FeS2 or FeS alone showed lower removal rates in the TCE removal process. The removal rate of TCE was relatively slow, and the final residual concentration was high.

[0101] Based on the above experimental results, it can be seen that M-SZVI 40 and M-SZVI 640 The removal efficiency is high, and the reasons are as follows.

[0102] Synergistic effect of lattice S doping:

[0103] M-SZVI sample: When FeS and FeS2 are added to the zero-valent iron for grinding, the mechanochemical process not only introduces the sulfidation reaction, but also dopes sulfur atoms into the zero-valent iron lattice. This S doping significantly changes the crystal structure of zero-valent iron, resulting in lattice distortion and increased defect sites. Sulfur doping forms abundant active sites in the iron lattice, improves electronic conductivity and surface reactivity, and thus enhances the reduction ability of Cr(VI) and TCE.

[0104] FeS or FeS2(SZVI 640 (D1) and SZVI 640 (D2)): The ball milling process of single sulfide is mainly surface sulfurization, and S doping is not significantly introduced. There are fewer active sites in the lattice, resulting in low electron transfer and reaction efficiency. The single sulfur source provided by FeS and FeS2 makes the structure of the sulfurized layer simple and cannot fully exert the synergistic effect. Therefore, the removal efficiency is far lower than that of the samples prepared by co-grinding.

[0105] Composite effects of different sulfides:

[0106] M-SZVI sample: FeS and FeS2 participate in the sulfidation process together, providing multiple sulfide reaction paths. The sulfidation of FeS is mild and uniform, while FeS2 has a strong sulfidation ability. The combination of the two can achieve a gradual and multi-level sulfidation reaction. This multiple sulfidation layer not only improves the corrosion resistance of the material, but also optimizes the electrochemical activity of the reaction interface, making the removal of Cr(VI) and TCE more efficient.

[0107] Using FeS or FeS2 alone: ​​The sulfide layer formed by a single sulfide is relatively simple and uneven, lacking diverse structures and reaction pathways, resulting in insufficient reaction activity. The sulfide layer formed by FeS is relatively mild but not active enough, while the layer formed by FeS2 may be over-sulfided, resulting in passivation of the reaction sites, both of which limit their ability to reduce pollutants.

[0108] Enhanced electron transfer capability:

[0109] M-SZVI 40 and M-SZVI 640 : Lattice S doping changes the electron density distribution, and the doped sulfur atoms can act as electron donors, significantly improving the electron transfer efficiency of the material. Sulfur doping also introduces more lattice defects and conductive channels, making the electron supply of zero-valent iron faster and more stable, thereby accelerating the reduction of Cr(VI) to Cr(III) and the dechlorination of TCE.

[0110] SZV 640 (D1) and SZVI 640 (D2): Due to the lack of lattice doping and mutual synergistic effects on the surface sulfide layer of a single sulfide, the electron transfer path is limited and insufficient electrons can be provided to participate in the reduction reaction, resulting in low removal efficiency.

[0111] More stable and dense vulcanizate layer:

[0112] M-SZVI sample: The sulfide zero-valent iron formed by co-grinding has a multi-layered dense sulfide layer, which can effectively protect the zero-valent iron core, extend the active life of the material, and provide continuous active sites. The complexity and stability of the sulfide layer ensure that the material maintains efficient pollutant removal capabilities for a long time.

[0113] FeS or FeS2 alone: ​​The sulfide layer is relatively simple and prone to passivation. During the reaction, the sulfide layer gradually loses its activity, resulting in a decrease in removal efficiency.

[0114] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing sulfur-doped zero-valent iron sulfide, characterized in that: The specific steps are as follows: S1, adding zero-valent iron, ferrous sulfide and pyrite into alcohol and stirring evenly to obtain a slurry to be ground; S2, loading grinding beads into a grinding tank of a wet ball mill, adding the slurry to be ground into the wet ball mill for grinding to obtain zero-valent iron sulfide particles, the grinding time is 40-640 min, the rotation speed of the wet ball mill is 1800-2200 rpm, and the grinding tank is provided with a stirrer, and the rotation speed of the stirrer is 100-140 rpm; S3, taking out the zero-valent iron sulfide particles from the wet ball mill, and placing the zero-valent iron sulfide particles into a magnetic separation device for separation; and S4, washing the separated zero-valent iron sulfide particles with ethanol, placing them in a vacuum drying oven, and drying them at a temperature of 55-65°C.

2. The method for preparing sulfur-doped zero-valent iron according to claim 1, Features: Wherein, the wet ball mill comprises: A ball milling chamber, used for loading ball milling beads and slurry to be ground, wherein a stirring shaft for stirring the ball milling beads and the slurry to be ground is provided inside the ball milling chamber; A feed tank, one end of which is connected to the ball milling chamber and is used to input the slurry to be ground into the ball milling chamber. The feed tank is provided with a stirrer for stirring the slurry to be ground evenly; and A centrifugal pump is connected to the ball milling chamber at one end and to the other end of the feed tank at the other end. The centrifugal pump is used to promote the return of the milled slurry in the ball milling chamber to the liquid storage tank to form a circulation.

3. The method for preparing sulfur-doped zero-valent iron according to claim 2, characterized in that: in, The rotation speed of the stirrer is 100-140 rpm.

4. The method for preparing sulfur-doped zero-valent iron according to claim 1, characterized in that: in, The zero-valent iron is flaky micron-sized zero-valent iron.

5. The method for preparing sulfur-doped zero-valent iron according to claim 1, characterized in that: in, The grinding beads are zirconium oxide grinding beads with a diameter of 0.3-0.5 mm, and the filling amount of the grinding beads is 0.7-0.8 kg.

6. The method for preparing sulfur-doped zero-valent iron according to claim 1, characterized in that: in, The grinding jar temperature of the wet grinder was controlled at 22-28°C.

7. The method for preparing sulfur-doped zero-valent iron according to claim 1, characterized in that: in, The mass ratio of the ferrous sulfide, pyrite and zero-valent iron is 1:(0.9-1.1):(15.5-16).

Citation Information

Patent Citations

  • Preparation method and application of sulfide-modified zero-valent iron composite material

    CN110627187B

  • Vulcanized micron zero-valent iron as well as preparation method and application thereof

    CN118341386A

  • Preparation method for iron-ferrous sulfide composite

    CN106536097A

  • Method for preparing composite zero-valent iron material based on soluble sulfide wet ball milling

    CN113102761A

  • Vulcanized and activated carbon-modified micron-sized zero-valent iron composite material as well as preparation method and application thereof

    CN116603501A

Cited By

  • Serine-grafted vulcanized nano zero-valent iron material as well as preparation method and application thereof

    CN122644087A